Maquiavelo, la excepción y la regla. Líneas de una investigación en curso - Ginzburg, Carlo (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2010)
Albeit that the relationship between scholarly tradition and the arguments set out by Brother Timothy in The Mandrake Root has been analysed on more than one occasion, the results have always remained in a hypothetical realm, attributing an indirect knowledge to Machiavelli thanks to Savonarola’s sermons on the writings of St. Bonaventure and St. Thomas Aquinas. In this article, several lines of investigation are explored, which, given Giovanni d’Andrea’s analysis of the Questiones mercuriales (a work found in Bernardo Machiavelli’s library) will not only allow a better knowledge of the form of Machiavelli’s work, but also a more profound investigation of the affinity which has so often been shown to exist between The Prince and The Mandrake Root; taking as a starting point the distinction formulated by d’Andrea between general principles (for example, the condemnation of usury) and the acquittal of certain principles which are informed by the circumstances, and therefore the consent to usury.